School Choice and Cognitive Achievement in Rural Bangladesh - Asadullah, Mohammad Niaz; Chaudhury, Nazmul; Dar, Amit (World Bank, Washington, DC, 2014)
This paper presents new evidence on the impact of school characteristics on secondary student achievement using a rich data set from rural Bangladesh. The authors deal with a potentially important selectivity issue in the South Asian context: the non-random sorting of children into religious schools. The authors do so by employing a combination of fixed effects and instrumental variable estimation techniques. Additionally, the authors use the variation between two classrooms of the same grade within individual schools to identify causal class-size effects. The empirical results do not reveal any difference in test scores between religious and secular schools when selection into religious school is taken into account. Net of school fixed-effects, the authors do not find evidence in support of smaller class size. However, they document significant learning deficit by gender and primary school type: girls and graduates of primary madrasas have a lower test score even after controlling for school and classroom-specific unobservable correlates of learning.